A comparison of the associations between alexithymia and both non‐suicidal self‐injury and risky drinking: The roles of explicit outcome expectancies and refusal self‐efficacy. (7th October 2020) - Greene, Danyelle; Hasking, Penelope; Boyes, Mark
Abstract: Both non‐suicidal self‐injury (NSSI) and risky drinking are positively associated with alexithymia, a personality trait characterized by difficulties appraising feelings and an externally orientated thinking style. Although researchers have studied the associations between alexithymia and both NSSI and risky drinking, the underlying factors of both associations are rarely compared. Using path analysis, we compared the mediating effects of behaviour‐specific outcome expectancies and self‐efficacy beliefs on the associations between alexithymia and both NSSI and risky drinking. A sample of 627 university students (76.10% female, Mage = 20.75, SD = 1.88) completed a battery of questionnaires. Alexithymia exhibited indirect effects on NSSI via affect regulation expectancies, pain expectancies, communication expectancies, and low self‐efficacy to resist NSSI. Alexithymia exhibited indirect effects on risky drinking via expectations of increased confidence and negative consequences. However, the indirect effects differed depending on the valance of the emotion the individual had difficulties appraising. Our findings indicate that the underlying factors in the associations between alexithymia and both NSSI and risky drinking could differ. Where individuals who have difficulties appraising negative emotions may engage in NSSI to help regulate negative feelings, they may consume alcohol to gain more confidence in expressing their feelings. Clinical implications are discussed.